IT Role in Fulfillment of Profit & Loss Sharing (PLS) Mechanism - Bidabad, Bijan; Allahyarifard, Mahmoud (International Journal of Islamic Banking and Finance Research, 2019)
In this paper, we are going to introduce a new IT master solution to improve non-usury banking performance. All divine religions emphasize on usury prohibition. It is concluded that with some IT solutions, it may be possible to fulfill the worldly requirement by use of IT systems without any incredulity. Since depositors are shareholders of Non-Usury Bank Corporation (NU Bank Co), therefore integrated information systems can provide suitable infrastructure for transactions recording and management done by all participants’ chains; and the end of process the yields of investment capital of depositors that invest in real economy can be distributed by safe delivery channels such as branches, ATM, WEB, Meaningful WEB. IT (as BPR, ERP, CRM, SCM, MES, MEX, HRM, WFM) that use single and integrated data warehouses) accompanying with standardization in all processes not only prepare PLS mechanism as main difference between conventional and non-usury banking but also simplify risk management and decline operational risk in comparison with conventional non-usury banking. Foundation of real non-usury banking can be based on an integrated IT system that links depositors, NU Bank Co, business partners, investors, stock exchange agencies, social security organization, certificate authorities (CA). Therefore, all related sectors may access the working flow of capital; IT processes, investment returns, and this causes stability in financial markets and achieve social justice establishment. In this paper, we are going to find a solution to this question: is it possible to connect depositors, bank, and investors in an integrated IT system to bring out PLS mechanism? Accordingly, we use a new kind of bank named by "Non-Usury Bank Corporation (Nu bank Co)" to fulfill the PLS criterion. This kind of non-usury bank will be capable of being established in different commercial law systems around the world. Thus, it will provide a suitable environment to automate non-usury banking operations that connect profits of depositors, bank, and loaners all together by using financial automatic communication channels.